2023
DOI: 10.1021/acs.langmuir.3c00322
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation by a Copper(II) Complex with 6,6′-Dihydroxy-2,2′-Bipyridine Ligand: Challenges and an Alternative Mechanism

Abstract: Recently, copper(II) complexes have been extensively investigated as oxygen-evolution reaction (OER) catalysts through a water-oxidation reaction. Herein, new findings regarding OER in the presence of a Cu(II) complex with 6,6′-dihydroxy-2,2′bipyridine ligand are reported. Using scanning electron microscopy, energy dispersive spectrometry, X-ray diffraction, Raman spectroscopy, in situ visible microscopy, in situ visible spectroelectrochemistry, X-ray absorption spectroscopy, and electrochemistry, it is hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…Similar to 1 , the Cu(II) ion is five coordinated in 2 and the CuN 2 OBr 2 coordination environment has distorted square pyramidal geometry with τ = 0.064. The Cu–N and Cu–O bond lengths in the equatorial positions of 2 are close to the similar bonds in 1 (see Table 2 ) and are in the normal range reported in similar Cu(II) complexes 68 71 . The Cu–Br1 and Cu–Br2 bond lengths are 2.3602(10) and 2.6607(10) Å, respectively and confirm their coordination to equatorial and axial positions and the presence of Jahn–Teller distortion in the axial direction.…”
Section: Resultssupporting
confidence: 81%
“…Similar to 1 , the Cu(II) ion is five coordinated in 2 and the CuN 2 OBr 2 coordination environment has distorted square pyramidal geometry with τ = 0.064. The Cu–N and Cu–O bond lengths in the equatorial positions of 2 are close to the similar bonds in 1 (see Table 2 ) and are in the normal range reported in similar Cu(II) complexes 68 71 . The Cu–Br1 and Cu–Br2 bond lengths are 2.3602(10) and 2.6607(10) Å, respectively and confirm their coordination to equatorial and axial positions and the presence of Jahn–Teller distortion in the axial direction.…”
Section: Resultssupporting
confidence: 81%
“…Visible diffuse reflectance spectroscopy (DRS) is a nondestructive analytical technique used to characterize the optical properties of solid materials. 8,9 Measuring the diffuse reflectance of a sample across a range of wavelengths in the ultraviolet and visible regions of the electromagnetic spectrum provides information about the electronic structure and composition of the material. 8,9 This technique is particularly valuable in studying pigments, catalysts, semiconductors, and other materials where traditional transmission-based spectroscopy may not be feasible.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…79 An alternative mechanism via Cu-complex decomposition and formation of a Cu thin film on the electrode was also proposed. 80 Papish and coworkers showed that reaction of CuSO 4 with 6,6′-dihydroxy-2,2′-bipyridine in ethylene glycol led to the formation of the well-defined Cu[N] 4 complex 32a that occurs in different protonation states depending on pH (Scheme 12, top). 81 Complexes 32 displayed moderate activity in the electrocatalytic water oxidation at even lower overpotential (447 mV) than the related postulated 1 : 1 adduct 31 .…”
Section: D Transition Metal Complexesmentioning
confidence: 99%